(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article examines the concept and essence of investment projects, investment lending and project financing, the role and importance of investment projects in the development of the country’s economy, the donation of international financial institutions and foreign banks in the formation of investment resources of commercial banks. Moreover, the possibilities of applying international experience in financing investment projects, the cooperation of commercial banks with the International Finance Corporation (IFC), the International Bank for Reconstruction and Development (IBRD), the European Bank for Reconstruction and Development (EBRD), the Asian Development Bank (ADB), as well as other development institutions were considered.